Approaching Ultimate Synthesis Reaction Rate of Ni-Rich Layered Cathodes for Lithium-Ion Batteries - Liu, Zhedong; Zhang, Jingchao; Luo, Jiawei; Guo, Zhaoxin; Jiang, Haoran; Li, Zekun; Liu, Yuhang; Song, Zijing; Liu, Rui; Liu, Wei‑Di; Hu, Wenbin; Chen, Yanan (Nano-Micro Letters, 2024)
Nickel-rich layered oxide LiNixCoyMnzO2 (NCM, x + y + z = 1) is the most promising cathode material for high-energy lithium-ion batteries. However, conventional synthesis methods are limited by the slow heating rate, sluggish reaction dynamics, high energy consumption, and long reaction time. To overcome these challenges, we first employed a high-temperature shock (HTS) strategy for fast synthesis of the NCM, and the approaching ultimate reaction rate of solid phase transition is deeply investigated for the first time. In the HTS process, ultrafast average reaction rate of phase transition from Ni0.6Co0.2Mn0.2(OH)2 to Li- containing oxides is 66.7 (% s−1), that is, taking only 1.5 s. An ultrahigh heating rate leads to fast reaction kinetics, which induces the rapid phase transition of NCM cathodes. The HTS-synthesized nickel-rich layered oxides perform good cycling performances (94% for NCM523, 94% for NCM622, and 80% for NCM811 after 200 cycles at 4.3 V). These findings might also assist to pave the way for preparing effectively Ni-rich layered oxides for lithium-ion batteries. Highlights: 1 A series of layered oxide cathode materials were synthesized by high-temperature shock strategy for the first time. 2 The approaching ultimate solid reaction rate of the layered nickel-rich layered oxide LiNixCoyMnzO2 was investigated for the first time. Ultrafast average reaction rate of phase transition from Ni0.6Co0.2Mn0.2(OH)2 to Li-containing oxides is 66.7 (% s-1), that is, taking only 1.5 s.